2013
DOI: 10.1007/s12263-013-0366-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of early transcriptome-based biomarkers related to lipid metabolism in peripheral blood mononuclear cells of rats nutritionally programmed for improved metabolic health

Abstract: Moderate maternal calorie restriction during lactation protects rat offspring against obesity development in adulthood, due to an improved ability to handle and store excess dietary fuel. We used this model to identify early transcriptome-based biomarkers of metabolic health using peripheral blood mononuclear cells (PBMCs), an easily accessible surrogate tissue, by focusing on molecular markers of lipid handling. Male and female offspring of control and 20 % calorierestricted lactating dams (CR) were studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…In addition, the transcriptome or gene expression analysis in PBMCs can reveal information on the lipid metabolism in obesity-associated organs, adipose tissue, and the liver [11]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the transcriptome or gene expression analysis in PBMCs can reveal information on the lipid metabolism in obesity-associated organs, adipose tissue, and the liver [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Advances in high-throughput technologies offer new opportunities to investigate the relationships between blood traits and body adiposity. Recent studies have shown differential expressions of several genes in blood peripheral cells that are associated with lipid handling in rats [3] and that are correlated with the development of visceral adiposity in humans [4]. Plasma proteomic profiles have…”
Section: Introductionmentioning
confidence: 99%
“…Afman et al 2014). Furthermore, it has been shown that PBMCs can act as biomarkers of the metabolic adaptations that occur in different tissues such as adipose tissue, liver and muscle (Caimari et al 2010a;Rudkowska et al 2011;Oliver et al 2013;O'Grada et al 2013;Konieczna et al 2014), although there are some controversial results about this issue (Rudkowska et al 2011;O'Grada et al 2013;Afman et al 2014). In addition, other studies have demonstrated that PBMCs can reflect gene expression signatures that are characteristic of different diseases linked to a sedentary lifestyle and increased food intake, such as atherosclerosis (Kang et al 2006), chronic heart failure (Cappuzzello et al 2009) and metabolic syndrome (D'Amore et al 2013).…”
Section: Introductionmentioning
confidence: 99%